COMPARATIVE ANALYSIS OF TECHNICAL AND TECHNICAL-FUNDAMENTAL MODELS FOR STOCK PRICE PREDICTION - Sabrinanur Ramadhani; Eneng Nur Hasanah (Jurnal Manajemen dan Bisnis Performa, 2026)
This study evaluates the predictive accuracy and risk-adjusted performance of Technical-Only (TO) and Technical-Fundamental (TF) forecasting models within the Indonesian equity market. Analysis of forecasting errors reveals that while the TO model offers superior consistency across diverse assets with a Mean Absolute Percentage Error (MAPE) consistently below 3.40%, the TF model provides enhanced precision for commodity-linked stocks like ANTM (1.30% error) but suffers from significant instability in speculative segments such as DEWA (10.40% error). Furthermore, while the TO model generated a higher nominal annualized return of 123.33%, the TF model demonstrated superior risk-adjusted efficiency by achieving a Sharpe Ratio of 1.65, matching the actual market benchmark and outperforming the TO model's 1.54. Consequently, the results suggest that while technical indicators provide a robust baseline for general price forecasting, the integration of fundamental filters is essential for achieving optimal risk-managed portfolio performance